2017
DOI: 10.1371/journal.pone.0177653
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic outcome following experimental infection of sheep with Chlamydia abortus variant strains LLG and POS

Abstract: This study investigated the pathogenesis of two variant strains (LLG and POS) of Chlamydia abortus, in comparison to a typical wild-type strain (S26/3) which is known to be responsible for late term abortion in small ruminants. Challenge with the three strains at mid-gestation resulted in similar pregnancy outcomes, with abortion occurring in approximately 50–60% of ewes with the mean gestational lengths also being similar. However, differences were observed in the severity of placental pathology, with infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 33 publications
4
20
1
Order By: Relevance
“…This suggests that, at least in terms of gross placental pathology, the lesions found in these vt infected placentas are very similar to those resulting from a typical wt infection. Furthermore, although there is a difference in the extent of the placenta affected, a very similar number of C. abortus genome copies were found by real-time qPCR within a specific pathological lesion.This is consistent with what has been observed in other studies [6], where although there has been little evidence of gross pathology we still observe high bacterial loads following qPCR analysis. Therefore, qPCR analysis of placental tissue, while not necessarily directly related to the extent of the gross pathology or the clinical outcome, is important for assessing any potential risk of transmission of infection to other naive animals.…”
Section: Plos Onesupporting
confidence: 93%
See 3 more Smart Citations
“…This suggests that, at least in terms of gross placental pathology, the lesions found in these vt infected placentas are very similar to those resulting from a typical wt infection. Furthermore, although there is a difference in the extent of the placenta affected, a very similar number of C. abortus genome copies were found by real-time qPCR within a specific pathological lesion.This is consistent with what has been observed in other studies [6], where although there has been little evidence of gross pathology we still observe high bacterial loads following qPCR analysis. Therefore, qPCR analysis of placental tissue, while not necessarily directly related to the extent of the gross pathology or the clinical outcome, is important for assessing any potential risk of transmission of infection to other naive animals.…”
Section: Plos Onesupporting
confidence: 93%
“…(typically 60-100% of the placental surface) the more likely that an abortion will occur (due to placental insufficiency resulting in a lack of nutrients and oxygenated blood getting to the fetus), but conversely there are instances where a heavily infected placenta is delivered following the birth of an 'apparently normal' live lamb [6]. Indeed, in this study, although vt-P1 exhibited around 60% gross pathology, the ewe delivered what appeared to be normal healthy lambs.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Lesions in the fetal lung consisted of neutrophil infiltration in alveoli, suppurative interstitial inflammation and interlobular edema and hemorrhage. The latter experimental study by Longbottom et al 97 was performed using the C. abortus strain S26/3, isolated from the placenta of a sheep that aborted due to OEA in Scotland, while the same authors 93 used strains LLG and POS, which have been isolated in Greece from aborted goat and sheep fetuses and which are genetically different to S26/3, in a recent comparative study. In doing so, they showed that the placental pathology, infectious load and serological response was clearly less pronounced for the strains LLG and POS than for the C. abortus strain S26/3.…”
Section: Chlamydia Abortus In Ruminants and Other Hostsmentioning
confidence: 99%